Processing plastic waste via pyrolysis-thermolysis into hydrogen and solid carbon additive to ethylene-vinyl acetate foam for cushioning applications - Wang, Yuxin (2024)
A strategy for enhancing value creation from pyrolysis gas and oil, derived from plastic waste, through the generation of two additional outputs of solid carbon and hydrogen was investigated. Three types of hard-to-recycle plastic waste (marine plastic litter, household mixed plastics and cosmetic products packaging) were thermally treated in two stages: (i) decomposition of feedstock into gas and oil via pyrolysis at 600 °C; and (ii) thermolytic conversion of the pyrolysis gas and a fraction of oil into hydrogen and solid carbon at 1300 °C separately. The thermolysis of both pyrolysis gas and oil fractions predominantly resulted in the production of solid carbon (39-70 wt% per plastic feedstock and carbon content of 91.3-98.6 wt%) and H2-rich gas (H2 yield of 5.9-10.8 wt% per plastic waste feedstock and H2 content of 71.4-97.2 vol% per gas volume). The incorporation of pyrolysis oil into the thermolysis process could enhance the outputs of solid carbon and hydrogen. Characterizations of solid carbon and hydrogen obtained from pyrolysis gas and oil fractions were further conducted. The observed similar properties of H2 and solid carbon from pyrolysis gas and oil supported the feasibility of introducing all the pyrolytic products together into the thermolysis process without condensation of oil. To enhance the value of these solid carbon derived from plastics for practical usage, we utilized the obtained solid carbon as a reinforcing agent for polymer composite foam development. The solid carbon reinforced composite foam displayed great abrasion resistance (wear loss: 240 mg), compression strength (0.347 MPa), and dynamic impact properties (energy returned: 124 J/m and energy absorbed: 57.3 J/m), emphasizing the viability of solid carbon as a nucleating agent and reinforcing filler in polymer foam for cushioning applications. Overall, the strategy of pyrolysis-thermolysis, which harnesses both pyrolysis gas and oil, unlocks additional value creation by producing two new outputs from plastic waste. Depending on the market prices for solid carbon and hydrogen, this can substantially change the economics of plastic waste management and create new revenue streams, incentivizing plastic waste collection and processing.